EFEKTIVITAS TEKNIK SCRAMBLE BERBANTUAN MEDIA KARTU BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN KELAS III SDN 20 AMPENAN - rizkya, anisah; Hadi Saputra, Heri; Erfan, Muhammad; Makki, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is based on the low early reading ability of students, as indicated by their difficulties in beginning reading. The aim of this study is to describe the use of the scramble technique assisted by picture card media in improving the early reading ability of third-grade students at SDN 20 Ampenan. This research uses a quantitative method with a quasi-experimental type and a pre-test post-test control group design. The sample consisted of two classes. Data were collected using pre-tests and post-tests in the form of performance-based reading tests. The results show that the scramble technique assisted by picture card media is quite effective in improving the early reading ability of students at SDN 20 Ampenan. This is indicated by an N-gain score of 65.10, which falls into the "quite effective" category, as well as an increase from a pre-test score of 58.46 to a post-test score of 85.3, showing a significant improvement in early reading ability.